Large‐Area MoS2 via Colloidal Nanosheet Ink for Integrated Memtransistor. Issue 11 (17th September 2021) - Nguyen, Duc Anh; Park, Dae Young; Duong, Ngoc Thanh; Lee, Kang‐Nyeoung; Im, Hyunsik; Yang, Heejun; Jeong, Mun Seok
Abstract: 2D transition metal dichalcogenides (TMDs) exhibit intriguing properties for applications in optoelectronics and electronics, among which memtransistors received extensive attention as multifunctional devices. For practical applications of 2D TMDs, large‐area fabrication of the materials via reliable processes, which is in trade‐off with their quality, has been a long‐standing issue. Here, a simple and effective way is proposed to fabricate large‐area and high‐quality molybdenum disulfide thin films using MoS2 colloidal ink through a spray coating, followed by a postsulfurization process. High‐quality MoS2 thin films exhibit excellent optical and electrical properties that can be utilized in field‐effect transistors (FETs) and memtransistor arrays. The MoS2 FETs show an average on/off ratio of 5 × 10 6 and a high electron mobility of 10.34 cm 2  V −1  s −1, which can be understood by the healing of sulfur vacancies, recrystallization, and the removal of the carbon contamination of the MoS2 . These MoS2 ‐based memtransistors present stable operations with a high switching ratio tuned by back gate and light illumination, which is promising for multiple‐levels memory and complex neuromorphic computing. This study demonstrates a new strategy to fabricate 2D TMDs with large‐area and high quality for integrated optoelectronic and memory device applications. Abstract : The large‐area and high quality MoS2 thin films are fabricated by spray coating of colloidal MoS2 nanosheets ink followed by a sulfurization processes. The sulfurized MoS2 film exhibits excellent optical and electrical properties, which is used to fabricate MoS2 array devices. MoS2 memtransistors show multiple switching states, which can be used to mimic biological synapses and neuromorphic computing systems.